Indikator Peran Pengawai Keuangan Publik dalam Menjamin Akuntabilitas Bumn PT Inka Persero di Kota Madiun - Zulfaidan Zubeir Batubara; Ammar Muhammad Zaky; Revienda Anita Fitrie; Eva Fany Fanida (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of the Financial and Development Supervisory Agency (BPKP) in improving the financial accountability of PT INKA (Persero) Madiun. This study uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that BPKP plays a role in improving financial accountability through internal audit activities, evaluation of internal control systems, and consultative functions to PT INKA management. This role has an impact on increasing compliance with financial regulations and improving corporate governance. However, the implementation of supervision still faces obstacles in the form of the complexity of company operations and limited supervisory resources. The conclusion of the study shows that the role of BPKP is quite significant in encouraging the financial accountability of PT INKA, although strengthening is needed through a risk-based supervisory approach and optimizing the use of information technology.